2018
DOI: 10.1186/s13018-018-0802-5
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intravenous aminocaproic acid in primary total hip and knee arthroplasty: a meta-analysis

Abstract: BackgroundWe conducted a meta-analysis from randomized controlled trials (RCTs) and non-RCTs to assess the efficacy of aminocaproic acid in cases of primary total hip arthroplasty (THA) or total knee arthroplasty (TKA).MethodsPotentially relevant academic articles were identified from the Cochrane Library, MEDLINE (1966–2017 October 31), PubMed (1966–2017 October 31), EMBASE (1980–2017 October 31), and ScienceDirect (1985–2017 October 31). Secondary sources were identified from the references of the included l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Antifibrinolytic agents have been tested for their functions of reducing the blood loss during various surgery [6][7][8]. Tranexamic acid (TXA) and epsilon-aminocaproic acid (EACA) are two such antifibrinolytic agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antifibrinolytic agents have been tested for their functions of reducing the blood loss during various surgery [6][7][8]. Tranexamic acid (TXA) and epsilon-aminocaproic acid (EACA) are two such antifibrinolytic agents.…”
Section: Introductionmentioning
confidence: 99%
“…EACA is another widely used antifibrinolytic agent to prevent or reduce bleeding in various procedures [ 11 ], such as total knee arthroplasty [ 7 ]. Not surprisingly, systematic application of EACA has also been reported to be associated with, though rare, various complications [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have shown that aminocaproic acid effectively reduces HBL during the perioperative period following total knee and total hip arthroplasty. 12,13 To the best of our knowledge, only a few studies so far have examined the role of aminocaproic acid in reducing perioperative HBL in femoral intertrochanteric fractures. Therefore, we conducted a prospective randomised controlled trial to determine the efficacy of aminocaproic acid in decreasing HBL in elderly patients with femoral intertrochanteric fractures undergoing the PFNA procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, blood management after THA is an important issue. Many kinds of techniques, including autologous fibrin tissue and aminocaproic acid, have been used to decrease bleeding and blood transfusion requirements after major orthopaedic surgery. Tranexamic acid (TXA) is a medication used to treat or prevent excessive blood loss from major trauma, postpartum bleeding, and surgery.…”
Section: Introductionmentioning
confidence: 99%